Pengaruh Bermain Aktif Terhadap Perkembangan Motorik Halus Anak Usia 3-5 Tahun Di Paud Lestari Desa Tegalbangsri Lumajang - Fitriyah, Nurul; E., Yessy Nur; Ermawati, Iit (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
The quality of growth and development in childhood determined of many aspects of life, including health, intellect, achievement and productivity in the future. The stage of children's fine motor development would be able to be achieved optimally as long as they got the right stimulation. In each phase, children need stimulation to develop their mental and fine motor skills, one of which was by active play. This study aimed to analyze the effect of active play on fine motor development. This research was a quasi-experimental research was a semi-treatment research. Data were taken before and after the active play treatment. According to the SDIDTK book, it was in the form of a developmental pre-screening questionnaire (KPSP) for children aged 3-5 years with a total sampling of 35 people. Data collection included coding, editing, tabulating and data were analyzed manually and computerized using the Wilcoxon test. The research respondents consisted of 12 men (34.28%) and 23 women (65.72%). The age of the respondents consisted of 3 years 11 people (31.42%), 4 years 20 people (57.14%) and 5 years 4 people (11.44%). In the pretest score, a minimum score of 3 was obtained and a maximum value of 10 with an average fine motor score of 7.54. In the post-test score, a minimum score of 5 and a maximum value of 10 were obtained with an average fine motor score of 8.37. Based on the results of the Wilcoxon statistical test, it was found that the p value <0.05, hypothesis was accepted, namely that there was an effect of active play on the fine motor skills of children aged 3-5 years. It was hoped that play group in Tegalbangsri Village, Ranuyoso District, would increase active play activities so that fine motor skills and the development of preschool age children are optimal.